JURIDICAL ANALYSIS RELATED TO DELAY NOTIFICATION OF THE ACQUISITION OF PT. LESTARI GEMILANG INTISAWIT FOR PT NABARI AGRO SUBUR - Mardiana Puspitasari; Rani Apriani (Jurnal Hukum Unsulbar, 2024)
Acquisition is a term for action taken by a company in acquiring assets in form of shares to increase market share. Legal issues that often arise related to company acquisition are related to delays in reporting to Commission for the Supervision for Bussiness Competition (Komisi Pengawas Persaingan Usaha) (KPPU). This legal research is a descriptive analysis type using a normative juridical approach through the applicable laws and regulations. Data collection techniques in this study used literature studies with primary and secondary data sources that are still related to the problems. Based on this research, it can be concluded that acquisititions are prohibited if they suspected of causing monopolistic practice and unfair business competition. In decision Number 05/KPPU-M/2022 PT. Lestari Gemilang Intisawit, which found to have commited violation, got sanction in form of fines in accordance with statutory regulations.